He oro hauora : how do kaupapa Māori models of health relate to my music therapy practice in an adolescent acute mental health unit? : an exegesis submitted to Massey University and Victoria University of Wellington in partial fulfilment of the requirements for the degree Master of Music Therapy, New Zealand School of Music - Hodgson, Nolan (Massey University, 2014)
This project explores the relationship between understandings of health within kaupapa Maori frameworks and music therapy with a particular focus on Durie’s Te Whare Tapa Wha (1998), Pere’s Te Wheke (1991) and ecological perspectives in music therapy. This research took place within an acute adolescent mental health unit that operates with a model of healthcare that emphasises Maori approaches to wellbeing. Secondary analysis of data involving techniques developed within grounded theory is used to investigate clinical notes from my music therapy practice in order to identify processes relevant to the four dimensions of Te Whare Tapa Wha. Themes that emerged were examined and used to investigate further data until a clearer picture of the relationship between music therapy and kaupapa Maori health frameworks became evident. This project particularly acknowledges the unique qualities of music and its practical application in music therapy in order to address and support a person's wairua within modern mental health practices. Specifically, the concepts of mana, mauri and whatumanawa appeared particularly relevant to the process of music therapy and the state of whakama also emerged as significant within this mental health context. Parallels between kaupapa Maori understandings of health and ecological perspectives within music therapy were also noted and particular reference made to the work of Carolyn Kenny and her Field of Play (2006) model in developing the discourse linking indigenous perspectives with the music therapy profession.
Keywords: Music therapy for teenagers; Mentally ill teenagers; Rehabilitation; Maori youth; Mental health services; New Zealand